Dissociable cognitive patterns related to depression and anxiety in multiple sclerosis. (September 2020) - Leavitt, Victoria M; Brandstadter, Rachel; Fabian, Michelle; Katz Sand, Ilana; Klineova, Sylvia; Krieger, Stephen; Lewis, Christina; Lublin, Fred; Miller, Aaron; Pelle, Gabrielle; Buyukturkoglu, Korhan; De Jager, Phillip L; et al.
Background: Individuals with multiple sclerosis (MS) frequently present with depression and anxiety, as well as cognitive impairment, challenging clinicians to disentangle interrelationships among these symptoms. Objective: To identify cognitive functions associated with anxiety and depression in MS. Methods: Mood and cognition were measured in 185 recently diagnosed patients (Reserve Against Disability in Early Multiple Sclerosis (RADIEMS) cohort), and an independent validation sample (MEM CONNECT cohort, n = 70). Partial correlations evaluated relationships of cognition to anxiety and depression controlling for age, sex, education, and premorbid verbal intelligence. Results: In RADIEMS cohort, lower anxiety was associated with better nonverbal memory ( rp = –0.220, p = 0.003) and lower depression to better attention/processing speed ( rp = –0.241, p = 0.001). Consistently, in MEM CONNECT cohort, lower anxiety was associated with better nonverbal memory ( rp = –0.271, p = 0.028) and lower depression to better attention/processing speed ( rp = –0.367, p = 0.002). Relationships were unchanged after controlling for T2 lesion volume and fatigue. Conclusion: Consistent mood–cognition relationships were identified in two independent cohorts of MS patients, suggesting that cognitive correlates of anxiety and depression are separable. This dissociation may support more precise models to inform treatment development. Treatment of mood symptoms may mitigate effects on cognition and/or treatment of cognition may mitigate effects on mood.